2015
DOI: 10.7717/peerj.1140
|View full text |Cite
|
Sign up to set email alerts
|

Composition, taxonomy and functional diversity of the oropharynx microbiome in individuals with schizophrenia and controls

Abstract: The role of the human microbiome in schizophrenia remains largely unexplored. The microbiome has been shown to alter brain development and modulate behavior and cognition in animals through gut-brain connections, and research in humans suggests that it may be a modulating factor in many disorders. This study reports findings from a shotgun metagenomic analysis of the oropharyngeal microbiome in 16 individuals with schizophrenia and 16 controls. High-level differences were evident at both the phylum and genus l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
147
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 225 publications
(173 citation statements)
references
References 106 publications
(112 reference statements)
9
147
2
5
Order By: Relevance
“…(Castro-Nallar et al, 2015) At the phylum level, schizophrenia samples exhibited higher proportions of Firmicutes across samples in comparison to controls; in the controls a higher relative proportion of Badteroidetes and Actinobacteria was observed. Regarding species diversity, controls were richer in the number of species compared to schizophrenia samples but less even in their distribution (Figure 1).…”
Section: Resultsmentioning
confidence: 97%
“…(Castro-Nallar et al, 2015) At the phylum level, schizophrenia samples exhibited higher proportions of Firmicutes across samples in comparison to controls; in the controls a higher relative proportion of Badteroidetes and Actinobacteria was observed. Regarding species diversity, controls were richer in the number of species compared to schizophrenia samples but less even in their distribution (Figure 1).…”
Section: Resultsmentioning
confidence: 97%
“…Higher incidence of lactic-acid bacteria in the oropharyngeal microbiome was reported, compared to controls (Castro-Nallar et al, 2015). Interestingly, a Lactobacillus specific phage was also discovered in high abundance (Yolken et al, 2015).…”
Section: The Microbiome In Neurodevelopmental and Mood Disordersmentioning
confidence: 99%
“…However, to date little systematic analysis has taken place in this field. In a small-scale study of the oro-pharyngeal microbiota alterations were observed (Castro-Nallar et al, 2015). A shotgun metagenomic analysis of the oropharyngeal microbiome in 16 individuals with schizophrenia and 16 controls was undertaken.…”
Section: Microbiota and Schizophreniamentioning
confidence: 99%